ETIKA MENUNTUT ILMU (STUDI KOMPARASI PEMIKIRAN AL-GHAZALI DAN ZARNUJI) - Gunawan Gunawan; Nana Jumhana; Rd Hidayatullah; Hasbullah Hasbullah (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2020)
Al-Ghazali and Zarnuji are two figures who have an international reputation, also have broad insights about the teachings of Islam. Even though both of them live in two countries with different cultures and cultures, they have the same vision and mission in eradicating ignorance and elevating human dignity, namely through education. In the process of education, each of the prosecutors of knowledge will experience a process of seeking and seeking knowledge, so that in the process has ethics and manners in studying.The formulation of the problem in research is How does ethics study Al-Ghazali's perspective? How does ethics study Zarnuji's perspective? How is the comparative analysis of Al Ghazali and Al Zarnuji's views on ethics studying? The purpose of this research is to find out the ethics of studying Al-Ghazali's perspective, to know the ethics of studying Zarnuji's perspective, to find out a comparative analysis of the views of Al Ghazali and Al Zarnuji about ethics studying. And the benefits are adding to the insight and knowledge of researchers about the ethics of studying in the perspective of Al-Ghazali and Al Zarnuji, to further serve as a reference in attitude and behavior.The method used is a descriptive qualitative research method with historical, textual and comparative approaches. As for the analysis technique, researchers used descriptive analysis techniques through a qualitative approach in the form of descriptions.The results of his research are Ethics studying in Al Ghazali's perspective there are ten points, while ethics studying in Al Zarnuji's perspective there are five points. Ethical equality in seeking knowledge in the view of Al Ghazali and Al Zarnuji is, to straighten out intentions accompanied by cleansing the heart and soul, the prosecutor of knowledge should not involve much in worldly affairs, he must respect and respect science, teachers, and experts. The difference in ethics requires that the perspective of Al Ghazali and Al Zarnuji be reviewed in terms of the nature of the prosecutor of knowledge, aspects of the teacher or instructor, as well as the qualifications of the knowledge pursued or demanded.